Determination of IL-8&inflammatory indicators (ESR,CRP) in Iraqi Multiple Sclerosis Patients (Journal of the College of Basic Education, 2022)
Multiple sclerosis (MS) is an inflammatory condition that affect the central nervous system (CSN) causing neurological dysfunction, the present study aimed to evaluate the role of Interleukin 8 (IL-8) and some inflammatory indicators: Erythrocytes Sedimentation Rate (ESR) and C Reactive Protein (CRP). Forty-five Iraqi MS patient and 15 apparently healthy control individuals were enroll in this study, the patients were attended the multiple sclerosis unit at consulting clinic of Baghdad teaching hospital at medicine city. During the period august – December 2014. The patient were clinically diagnosed by the consultant medical staff at the clinic, which was based on a clinical examination, magnetic resonance image (MRI), immunological tests, and under the supervision of this staff. The patients were divide into: (Untreated patients, Patients treated with methylprednisolone, Patients treated with interferon beta).